2018
DOI: 10.1200/jco.2017.74.5497
|View full text |Cite
|
Sign up to set email alerts
|

Patient Age–Associated Mortality Risk Is Differentiated by BRAF V600E Status in Papillary Thyroid Cancer

Abstract: For the past 65 years, patient age at diagnosis has been widely used as a major mortality risk factor in the risk stratification of papillary thyroid cancer (PTC), but whether this is generally applicable, particularly in patients with different BRAF genetic backgrounds, is unclear. The current study was designed to test whether patient age at diagnosis is a major mortality risk factor. Patients and MethodsWe conducted a comparative study of the relationship between patient age at diagnosis and PTCspecific mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 37 publications
10
89
0
3
Order By: Relevance
“…These data corroborate findings in a large 459 patient study from the University of California, San Francisco, in which BRAF V600E mutation was also not associated with negative clinicopathologic factors . In a recent publication, BRAF V600E mutation did not worsen cancer‐specific mortality in patients <45 years old . Thus, the association of BRAF V600E mutation with aggressive PTC pathology and clinical recurrence remains unclear.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These data corroborate findings in a large 459 patient study from the University of California, San Francisco, in which BRAF V600E mutation was also not associated with negative clinicopathologic factors . In a recent publication, BRAF V600E mutation did not worsen cancer‐specific mortality in patients <45 years old . Thus, the association of BRAF V600E mutation with aggressive PTC pathology and clinical recurrence remains unclear.…”
Section: Discussionsupporting
confidence: 85%
“…19 In a recent publication, BRAF V600E mutation did not worsen cancer-specific mortality in patients <45 years old. 20 Thus, the association of BRAF V600E mutation with aggressive PTC pathology and clinical recurrence remains unclear. The lack of association between BRAF mutation and MAPK (dpERK) activation at the protein level in PTCs could partially explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current prognosis evaluation system of thyroid cancer, the patient's age is a recognized risk factor for death; various clinical guidelines and risk assessment models include the patient's age as the primary risk factor in the management and prognostic evaluation of thyroid cancer. The presence of the BRAF mutation is closely related to the patient's age; thus, there may be synergistic effects leading to a poor prognosis [33]. Therefore, in the risk assessment of PTC patients, the BRAF gene mutation and the patient age should be considered as factors associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of thyroid cancer remains unclear to date. Numerous studies have identified a number of risk factors for PTC, such as old age, female sex, radiation exposure, high body surface area and weight changes, and gene BRAF V600E mutation . These factors are all reportedly associated with poor clinical outcomes of PTC, including extrathyroidal extension, lymph node metastasis, and distant metastasis.…”
Section: Introductionmentioning
confidence: 99%